Optimisation of soaking and thermal processing methods in reducing the trypsin, chymotrypsin and alpha-amylase inhibitors found in underutilised legumes for use as aquafeed - Choi, Wai Chuen (2018)
In carnivorous fish farming industry, there are progressive increase demands for the finite resource of fish meal. A potential alternative to fish meal is to use legume meals which are free of enzyme inhibitors. In selected underutilised legumes the most effective processing method for eliminating trypsin (TIA), chymotrypsin (CIA) and alpha-amylase (AIA) inhibitors, without affecting the crude protein content, was investigated. These methods included soaking (S), wet heating (W), autoclaving (A) and dry freezing (D). No single method was effective at removing all the inhibitors. In all legumes tested, the combined processing methods which involved A were most effective in reducing CIA and AIA (p<0.05), but not TIA. However, in adzuki bean both TIA and CIA were reduced by the D+A combined method (p<0.05), whereas AIA of soybean and adzuki bean was decreased by combined methods of S+A (84.7 % and 99.3 % reduction respectively, p<0.05) or A+D (99.1 % and 72.6 % reduction respectively, p<0.05). All the processing methods retained 86.5 – 90.5 % of crude protein. Replacement of 10 % (w/w) of fish meal with D+A treated legume meal (either bambara groundnut or adzuki bean) for 28 days showed no significant difference in growth performance or inflammatory effects in Danio rerio or Lates calcarifer. Compared to Lates calcarifer given feed containing unprocessed adzuki bean meal, those on feed containing processed adzuki bean meal had increased hepatic gene expression of alanine aminotransferase (p<0.01), indicating an enhanced ability to utilise amino acids. The project identified specific food processing methods which are effective at removing enzyme inhibitors in legumes, thereby facilitating the application of legumes as aquafeed ingredients. Future studies are required to examine what inclusion level of treated legume meal can promote growth performance in specific commercial fish species.